Fluctuations in Oxygen Saturation during Synchronized Nasal Intermittent Positive Pressure Ventilation and Nasal High-Frequency Oscillatory Ventilation in Very Low Birth Weight Infants: A Randomized Crossover Trial - Atanasov, Svilen; Dippel, Constanze; Takoulegha, Dupleix; Windhorst, Anita; Schuler, Rahel; Strodthoff, Claas; Frerichs, Inéz; Dreyhaupt, Jens; Waitz, Markus; Sohrabi, Keywan; Ehrhardt, Harald; Justus Liebig University Giessen (My University, 2023)
Background: Very low birth weight (VLBW) infants on noninvasive ventilation (NIV) experience frequent fluctuations in oxygen saturation (SpO2) that are associated with an increased risk for mortality and severe morbidities. Methods: In this randomized crossover trial, VLBW infants (n = 22) born 22+3 to 28+0 weeks on NIV with supplemental oxygen were allocated on two consecutive days in random order to synchronized nasal intermittent positive pressure ventilation (sNIPPV) and nasal high-frequency oscillatory ventilation (nHFOV) for 8 h. nHFOV and sNIPPV were set to equivalent mean airway pressure and transcutaneous pCO2. Primary outcome was the time spent within the SpO2 target (88–95%). Results: During sNIPPV, VLBW infants spent significantly more time within the SpO2 target (59.9%) than during nHFOV (54.6%). The proportion of time spent in hypoxemia (22.3% vs. 27.1%) and the mean fraction of supplemental oxygen (FiO2) (29.4% vs. 32.8%) were significantly reduced during sNIPPV, while the respiratory rate (50.1 vs. 42.6) was significantly higher. Mean SpO2, SpO2 above the target, number of prolonged (>1 min) and severe (SpO2 <80%) hypoxemic episodes, parameters of cerebral tissue oxygenation using NIRS, number of FiO2 adjustments, heart rate, number of bradycardias, abdominal distension and transcutaneous pCO2 did not differ between both interventions. Conclusions: In VLBW infants with frequent fluctuations in SpO2, sNIPPV is more efficient than nHFOV to retain the SpO2 target and to reduce FiO2 exposure. These results demand more detailed investigations into cumulative oxygen toxicities during different modes of NIV over the weaning period, particularly with regard to consequences for long-term outcomes.
Keywords: ddc:610